2019
DOI: 10.1101/780742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CpG-ODN 2007 protects zebrafish against Vibrio vulnificus-induced infection

Abstract: Vibrio vulnificus (V. vulnificus) is an aquatic pathogen that can cause primary sepsis and soft tissue infection. CpG oligodeoxynucleotides (CpG-ODN) are a type of essential immunomodulators, which can trigger or enhance immune responses in mammals, fish, and humans. In this study, we evaluated the effect of CpG-ODN 2007 as a potential immunostimulant for zebrafish infected with V. vulnificus (FJ03-X2). Fish injected with the CpG-ODN 2007 showed lower mortality rate compared with the fish that did not receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Vibrio vulnificus, that is an aquatic pathogen that can cause primary sepsis and soft tissue infection, was also tested during an experimentation of zebrafish's reaction to vaccine. It was concluded that CpG oligodeoxynucleotides, a type of essential immunomodulators, protected zebrafish against Vibrio vulnificus induced infection [15].…”
Section: Fish Vaccinesmentioning
confidence: 99%
“…Vibrio vulnificus, that is an aquatic pathogen that can cause primary sepsis and soft tissue infection, was also tested during an experimentation of zebrafish's reaction to vaccine. It was concluded that CpG oligodeoxynucleotides, a type of essential immunomodulators, protected zebrafish against Vibrio vulnificus induced infection [15].…”
Section: Fish Vaccinesmentioning
confidence: 99%